2008
DOI: 10.5142/jgr.2008.32.3.238
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Characteristics of White, Fermented and Red Ginseng Extracts

Abstract: :Comparison of the physico-chemical characteristics were investigated among white (WG), fermented (FG) and red ginseng (RG) extracts. We observed maximum contents of extractable solids in FG, but viscosity was lower than other ginseng extracts. The contents of ash and crude protein of FG were higher than those of other ginseng extracts. The contents of carbohydrate were similar, but component Na and cruid lipids were maximum in RG. we extended our study on comparison of the calories among WG, FG and RG. We n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The contents of quercetin in the samples, outer layers of aloe leaf extracts (AW) and the fermented extract (AF) were measured as 3.45 mg/g and 3.31 mg/g, respectively, and their concentrations were much higher than the value of 0.012 mg/g detected in the gels from Aloe vera [32], while other studies have also reported similar contents of quercetin in Aloe vera ranging from 0.093 to 10.94 mg/g, depending on the parts examined [33][34][35]. This result would support the advantage of fermenting the plant resources to have higher elution of bioactive substances [18][19][20]. In particular, the outer layers of Aloe vera contained much higher amounts of quercetin than the gels that are most often consumed, and a similar result was also reported in another study [36].…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The contents of quercetin in the samples, outer layers of aloe leaf extracts (AW) and the fermented extract (AF) were measured as 3.45 mg/g and 3.31 mg/g, respectively, and their concentrations were much higher than the value of 0.012 mg/g detected in the gels from Aloe vera [32], while other studies have also reported similar contents of quercetin in Aloe vera ranging from 0.093 to 10.94 mg/g, depending on the parts examined [33][34][35]. This result would support the advantage of fermenting the plant resources to have higher elution of bioactive substances [18][19][20]. In particular, the outer layers of Aloe vera contained much higher amounts of quercetin than the gels that are most often consumed, and a similar result was also reported in another study [36].…”
Section: Discussionsupporting
confidence: 46%
“…Therefore, it is necessary to develop a technique for processing the relatively hard parts of Aloe vera while maintaining its good efficacies to utilize this leaf skin efficiently. Lactic acid fermentation could primarily be considered since this process is operated under low temperature and mild extraction conditions, which would not degrade the bioactive substances in leaf skin [18,19]. The fermentation process has also been shown to improve the elution yields of active components from natural resources, especially the hard structures of the plants, along with the bioconversion of its metabolites, which increase its efficacies by promoting synergistic effects with various components in the extracts [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng contains carbohydrates (60% to 70%), nitrogen compounds (12% to 16%), saponin (3% to 6%), fat-soluble compounds (1% to 2%), minerals (4% to 6%), and vitamins (0.05%) [2]. Physiological activities of ginseng include a nourishing and strengthening effect, improved reproductive function, anti-hypertension and anti-arteriosclerosis, an anemia-treating effect, a glucose metabolism and diabetes improving effect, anticancer, hepatic function improving effect, hangover relieving effect, parasite infection prevention, and analgesic and anti-inflammatory effects, which have been studied through systematic pharmacological approaches.…”
Section: Introductionmentioning
confidence: 99%